2022
DOI: 10.1021/acsomega.2c01922
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antimicrobial Activity and Biocompatibility of Biogenic Silver Nanoparticles Synthesized using Syzigyum cymosum Extract

Abstract: Nanotherapeutics has emerged as the most sought after approach to tackle the menace of drug-resistant pathogenic bacteria. Among others, biogenic silver nanoparticles (bAgNPs) synthesized using medicinal plant extracts demonstrate promising antibacterial propensity with excellent biocompatibility. Herein, bAgNPs were synthesized through the green chemistry approach using Syzygium cymosum leaf extract as a reducing agent at different pH values (i.e., 5, 7, 8, and 10). The average size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Several reports provide contrasting evidence on the biocompatibility and toxicity of MNPs. For instance, several reports highlighted the biocompatibility of AuNPs and HAuNPs at cellular, in vivo , and at nonhuman primate levels. ,, On the other hand, Rathore et al and Zhang et al reported that AuNPs exert toxic effects. More interestingly, Zhang et al reported the route of administration-based AuNP toxicity with i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports provide contrasting evidence on the biocompatibility and toxicity of MNPs. For instance, several reports highlighted the biocompatibility of AuNPs and HAuNPs at cellular, in vivo , and at nonhuman primate levels. ,, On the other hand, Rathore et al and Zhang et al reported that AuNPs exert toxic effects. More interestingly, Zhang et al reported the route of administration-based AuNP toxicity with i.v.…”
Section: Resultsmentioning
confidence: 99%
“…A similar contrasting toxicity profile is reported for AgNPs. For instance, Qiu et al, 68 Mahmud et al, 69 and Lin et al 59 highlighted the biocompatible nature of AgNPs. On the other hand, AshaRani et al 60 and Souza et al 61 reported AgNPs as genotoxic agents.…”
Section: Biocompatibility and Biodistribution Studiesmentioning
confidence: 99%
“…XRD patterns of bAgNPs were analyzed using a powder X-ray diffractometer (GNR Xray Explorer, Italy) following our previously published protocol. 4,10,11…”
Section: Characterization Of Biogenic Silver Nanoparticles (Bagnps)mentioning
confidence: 99%
“…Furthermore, rats treated with bAgNPs exhibited no significant toxicity in terms of their hematological and biochemical parameters. 4,[10][11][12] This is due to the presence of secondary metabolites such as saponins, flavonoids, terpenoids, and quinines in plant extracts, which have strong reducing potential and lead to the production of nanoparticles with better characteristics. 4 As a result, silver nanoparticles made from plant extracts have a natural ability to combat various bacterial strains, including those that are resistant to multiple drugs, while also being more biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of nanoparticles (NPs) has assisted in the evolution of traditional RT from a “one-size-fits-all” concept to tailored and dynamic treatment modalities [ 13 ]. High surface-to-volume ratios, increased cellular uptake, and adjustability make NPs a suitable choice for tumor-targeted and less toxic treatment approaches [ 24 , 25 , 26 , 27 , 28 , 29 ]. NPs that are prepared from high Z materials act as radiosensitizers, receiving external beams of ionizing radiation [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%